A Robust Fast Fracture Plane Orientation Angle Search Algorithm for Puck 3D Inter-Fibre Failure Criterion - Wirawan, Nanda; Abuzayed, Ibrahim H.; Akbar, Mahesa; Curiel-Sosa, Jose L. (European Journal of Computational Mechanics, 2024)
In the present work, a novel fast fracture plane orientation angle (FPOA) search algorithm for the 3D Puck failure criterion is proposed. In the 3D Puck failure criterion, a linear search algorithm is employed to calculate the maximum inter-fibre failure (IFF) value by iterating and comparing the IFF value for each FPOA. This process itself requires a substantial amount of computational resources. The proposed fast FPOA search algorithm is implemented to substitute the linear search algorithm in order to reduce the computational time. A total of 1×105 randomised stress cases are used to analyse the accuracy of the algorithm. The result was then compared with the Puck Stepwise Seach Method (SSM) and other fast FPOA search algorithms. The results show that the proposed fast FPOA search algorithm has better accuracy compared to the other fast FPOA search algorithms and is almost 5 times faster compared to the SSM algorithm by Puck. In addition, a subroutine contains the Puck failure criterion and the proposed fast FPOA search algorithm is embedded into a Finite Element Analysis (FEA) software to simulate the open-hole test (OHT) experiment on the composite material.